(untitled) (Proceedings of International Educators Conference, 2023)
This article focuses on the mechanism of operation and effectiveness of the online trading platform, using FOM.UZ as an example. The study uses a combination of methods, including a review of literature, observation of the platform’s operation, and interviews with platform users. The results show that the platform is effective in facilitating trading activities, providing access to information, and enabling transactions. However, there are also challenges that need to be addressed to further enhance the platform’s performance.